APLIKASI NITROGEN (N) MELALUI SISTEM IRIGASI KENDI PADA BUDIDAYA TOMAT (LYCOPERSICUM ESCULENTUM MILL) - Aloysius Ng. Lende (Partner, 2013)
Nitrogen Application through Pitcher (Jug) Irrigation System on Tomato Culture. Tomato plants require nitrogen for leaf formation and good quality fruit production. In order to be efficienctly and effectively using the nitrogen fertilizer, it is recommended to apply a pitcher irrigation sistem. The aim of this research is to find out the effect of the combination of nitrogen dose and main material composition of pitcher that may increase the yield of tomato. The research has been done in Naimata village in Kupang City, started from June until September 2009. The Experimental design used in this research was Randomized Complete Block Design with nine treatments and three replications. The results showed that the effect of the combined treatments to plant height at age of 35 days after planting with the highest number was on 200 kg N.ha-1and pitcher type  2 (75% of clay ; 15% of sand ; 10% of sawdust) treatment (87,09), the number of fruits of each plant was highest in 150 kg N ha-1and pitcher type  2 (75% of clay; 15% of sand ; 10% of sawdust) treatment (195,33), and fresh fruit per plants was highest in 150 kg N ha-1and pitcher type  2 (75% of clay; 15% of sand; 10% of sawdust) treatment  (9118,10).Keywords: Nitrogen, Pitcher and Tomato